Different toxicity of cadmium telluride, silicon, and carbon nanomaterials against hemocytes in silkworm, Bombyx mori. Issue 79 (30th October 2017) - Li, Kai-Le; Zhang, Yun-Hu; Xing, Rui; Zhou, Yan-Feng; Chen, Xue-Dong; Wang, Hao; Song, Bin; Sima, Yang-Hu; He, Yao; Xu, Shi-Qing
Abstract : Exposure to CdTe QDs, SiNPs, or C–NCDs exerted different toxic effects on silkworm hemocytes via the induction of different PCD processes. Abstract : The biological toxicity of nanomaterials is a concern because they have many potential applications in biomedical fields. In this study, silkworm hemolymph was exposed to high-dose cadmium telluride quantum dots (CdTe QDs), citric-acid–nitrogen-doped carbon dots (C–NCDs), or silicon nanoparticles (SiNPs) and the differences in the immune responses and programmed cell death induced in hemocytes were compared. Changes in the expression of innate-immunity-related genes and the occurrence of hemocytes in the hemolymph indicated that the three types of nanomaterials entered several types of hemocytes by endocytosis, but their toxicity differed significantly. C–NCDs only induced autophagy in the hemocytes, whereas SiNPs induced both hemocyte autophagy and the simultaneous apoptosis of a large number of cells. CdTe QD exposure rapidly induced hemocyte apoptosis and necrosis. The mechanisms of hemocyte apoptosis induced by the different nanomaterials differed significantly. The apoptosis induced by CdTe QDs was dependent on the lysosomal apoptotic pathway, whereas SiNPs also used the endoplasmic reticulum apoptotic pathway. The autophagy and even apoptosis that appeared in the hemocytes after SiNP exposure quickly self-repaired, whereas the autophagy induced in hemocytes by C–NCD exposure persisted.